The Female Gaze in Mad Men: Study of the Audiovisual Point of View - Gutiérrez-Martínez, Begoña (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The main objective is to find out in which proportion viewers access the subjective point of view of the female characters in the series Mad Men (Matthew Weiner, 2007-2015). To this end, we focus on the analysis of the pilot, Smoke Gets in Your Eyes (Alan Taylor, 2007). We employ a methodology of quantitative and qualitative analysis of the audiovisual text. For the extraction of quantitative data we use Encuadres, software created by Professor Jesús González Requena. We then carry out a textual analysis of those moments in which we gain access to the subjective point of view of the female characters in the series.